2020
DOI: 10.31436/imjm.v19i2.1567
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity, Body Mass Index and Body Composition among Students at a Pre-University Centre in Malaysia

Abstract: INTRODUCTION: Physical activity is an essential element in our daily life that leads to long-term health benefits. Physical activity refers to movement of the body that requires energy. Body mass index (BMI) indicates a ratio of body weight to squared height, which is a useful health indicator. On the contrary, body composition describes the body by measuring percentages of fat and muscle in human bodies. MATERIALS AND METHODS: This cross-sectional study aimed to determine the relationship between physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Present study found that a negative correlation between physical activity and BMI. This is similar to a study done by Tan PL et al (15) they found that the relationship between physical activity and BMI indicates a very weak negative correlation (r=-0.084). They concluded that when physical activity increases, BMI and body fat mass would decrease.…”
Section: Discussionsupporting
confidence: 91%
“…Present study found that a negative correlation between physical activity and BMI. This is similar to a study done by Tan PL et al (15) they found that the relationship between physical activity and BMI indicates a very weak negative correlation (r=-0.084). They concluded that when physical activity increases, BMI and body fat mass would decrease.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this study also revealed that there was a negative correlation between PAL and BMI among students, and moderate PAL was presented with the highest percentage compared to low and vigorous PAL. This finding is similar to a study among pre-university students in Malaysia in which 50% of students were minimally active and there was a negative correlation between PAL and BMI, however, the relationship was very weak (You et al, 2020). A systematic study reported that a few factors have been associated with low PAL among university students including lack of suitable facilities, longer time on screen time, and academic-related activities (Ferreira Silva et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, physical activity can also influence BMI status. A study among students in a public university in Malaysia revealed that the prevalence of students minimally active achieved half of them and only 30% of them were physically active while there was a negative correlation between BMI status and PAL among students (You et al, 2020). Additionally, it was reported from another study among university students that there was a significant association between PAL and BMI status in which active students have a 0.4 times lower risk for overweight or obesity (Tapera et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity affected BMI values and body composition. 7 Despite the importance of having a normal BMI and being physically active, a study showed that as many as 30% of respondents were overweight and obese, the majority of whom spent about 5 hours a day physically inactive. 8 Based on the research conducted in Indonesia, population groups with high socio-economic status were more at risk of obesity because the higher the amount of food income, the more consumptive behavior towards food and drink appeared, and individuals with high socioeconomic status generally had busy jobs, so physical activity decreased.…”
Section: Introductionmentioning
confidence: 99%